BATIK BEKAL: Design of a Differentiated Mathematics Learning Website Based on Kasumedangan Local Wisdom - M. Nuur’aini Sholihat; Ucu Koswara; Dedi Irawan; Yusfita Yusuf; Dilsa Sabina Azizah (Jurnal Inovasi Matematika, 2026)
Mathematics education in Indonesia continues to face challenges in accommodating diverse student characteristics and connecting mathematical concepts with meaningful cultural contexts. Uniform and procedural teaching practices often hinder the development of conceptual understanding and mathematical literacy. Although differentiated instruction and the integration of local wisdom have been discussed extensively, studies that systematically integrate both within digital mathematics learning media remain limited. This study aims to develop and evaluate BATIK BEKAL (Learning Mathematics through Local Wisdom), a web-based mathematics learning platform integrating differentiated instruction with Kasumedangan local wisdom. The study employed a Research and Development (R&D) approach using the ADDIE model. Participants included 50 mathematics teachers involved in the needs analysis and 25 junior high school students in a limited classroom implementation. Data were collected through questionnaires, expert validation instruments, classroom observations, and semi-structured interviews. The results indicate that the developed platform demonstrates high pedagogical, technical, and cultural validity and is perceived as practical by both teachers and students. The integration of local wisdom functions as a conceptual scaffold within differentiated mathematics learning. These findings contribute to the development of culturally responsive and adaptive digital mathematics learning media.